Application of eye trackers for understanding mental disorders: Cases for schizophrenia and autism spectrum disorder. Issue 2 (2nd February 2019) - Shishido, Emiko; Ogawa, Shiori; Miyata, Seiko; Yamamoto, Maeri; Inada, Toshiya; Ozaki, Norio
Abstract: Studies of eye movement have become an essential tool of basic neuroscience research. Measures of eye movement have been applied to higher brain functions such as cognition, social behavior, and higher‐level decision‐making. With the development of eye trackers, a growing body of research has described eye movements in relation to mental disorders, reporting that the basic oculomotor properties of patients with mental disorders differ from those of healthy controls. Using discrimination analysis, several independent research groups have used eye movements to differentiate patients with schizophrenia from a mixed population of patients and controls. Recently, in addition to traditional oculomotor measures, several new techniques have been applied to measure and analyze eye movement data. One research group investigated eye movements in relation to the risk of autism spectrum disorder several years prior to the emergence of verbal‐behavioral abnormalities. Research on eye movement in humans in social communication is therefore considered important, but has not been well explored. Since eye movement patterns vary between patients with mental disorders and healthy controls, it is necessary to collect a large amount of eye movement data from various populations and age groups. The application of eye trackers in the clinical setting could contribute to the early treatment of mental disorders. Abstract : Studies of eye movement have become an essential tool of basic neuroscience research. With the development of eye trackers, a growing body of research has described eye movements in relation to mental disorders.